Technology blueprint : Sanismart / Adlina Anati Abdul Aziz, Ain Nazira Mohd Tahir and Lyana Ibrahim - Abdul Aziz, Adlina Anati; Mohd Tahir, Ain Nazira; Ibrahim, Lyana (2021)
SaniSmart is created to enhance and innovate existing products, with the consumers' needs in mind. The target market for this new product development are healthcare services staff, delivery services workers, as well as full and part time workers where their jobs require them to be outside and meeting people, which could make them more at risk of being infected by Covid- 19.